Respuesta :
Given the polynomial equation x^3 -6x = 3x^2 – 8. Which can be simplified into (x^3) -3(x^2) -6x +8 = 0. The roots of the given equation are x = -2, x = 1 and x = 4. The order of equation also represents the number of roots of the equation given. Since the highest exponent is 3, there also 3 roots. So the answer is D. 2 –2, 1, 4
x^3 -6x = 3x^2 -8
x^3 - 3x^2 -6x = -8
x^3 - 3x^2 -6x +8 = 0
now factor:
(x-4) (x^2+x-2) = 0
(x-4) (x-1)(x+2) = 0
the roots are 4, 1, -2
answer is the last one